165k views
1 vote
Solve the equation: 4 - 5(3- 2x) = -2x + 1

User Stichy
by
5.1k points

2 Answers

5 votes

Answer:x=1

4 - 5(3- 2x) = -2x + 1

4 - 15 +10x = -2x+1

-11 +10x = -2x+1

-11+10x+2x = -2x+2x +1

-11+12x = 1

-11 +11 + 12x = 11+1

12x = 12

12x/12 = 12/12

x =1

User Nivendha
by
4.5k points
3 votes

Answer:

x=1

Explanation:

4 - 5(3- 2x) = -2x + 1

Distribute

4 - 15 +10x = -2x+1

Combine like terms

-11 +10x = -2x+1

Add 2x to each side

-11+10x+2x = -2x+2x +1

-11+12x = 1

Add 11 to each side

-11 +11 + 12x = 11+1

12x = 12

Divide each side by

12x/12 = 12/12

x = 1

User Scw
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.